Acetylation of intrinsically disordered regions regulates phase separation - Saito, Makoto; Hess, Daniel; Eglinger, Jan; Fritsch, Anatol W.; Kreysing, Moritz; Weinert, Brian T.; Choudhary, Chunaram; Matthias, Patrick (Nature chemical biology, 2019)
Liquid–liquid phase separation (LLPS) of proteins containing intrinsically disordered regions (IDRs) has been proposed as a mechanism underlying the formation of membrane-less organelles. Tight regulation of IDR behavior is essential to ensure that LLPS only takes place when necessary. Here, we report that IDR acetylation/deacetylation regulates LLPS and assembly of stress granules (SGs), membrane-less organelles forming in response to stress. Acetylome analysis revealed that the RNA helicase DDX3X, an important component of SGs, is a novel substrate of the deacetylase HDAC6. The N-terminal IDR of DDX3X (IDR1) can undergo LLPS in vitro, and its acetylation at multiple lysine residues impairs the formation of liquid droplets. We also demonstrated that enhanced LLPS propensity through deacetylation of DDX3X-IDR1 by HDAC6 is necessary for SG maturation, but not initiation. Our analysis provides a mechanistic framework to understand how acetylation and deacetylation of IDRs regulate LLPS spatiotemporally, and impact membrane-less organelle formation in vivo. HDAC6 modulates acetylation at multiple lysine residues in the N-terminal intrinsically disordered region of RNA helicase DDX3X to regulate liquid–liquid phase separation and stress granule maturation.